Reprint of “Assessing evictions and expropriations in China: Efficiency, credibility and rights” - Pils, Eva (Land Use Policy, 2018)
Examining three possible ways of interpreting China's laws on expropriation and eviction, I argue in this paper that a persuasive evaluative assessment of China's property regime needs to examine the impact of forced evictions not only on property rights but also on basic rights such as the human right to be protected from forced evictions, and the problem of access to justice in cases of contentious evictions. Some (neo-liberal) arguments for secure property rights, while popular, are based on a simplistic understanding of rights, because they reduce the value of rights to their assumed utility. The ‘credibility' thesis advanced by Peter Ho can be used to assess evictions under China's property rights and land tenure system, but according to the view taken here, a truly credible system must protect basic rights.
CRIS-Team Scopus Importer:2023-03-21
Keywords: China; Credibility thesis; Eviction; Expropriation; Human rights; Land tenure; Neo-liberalism; Property rights; Takings